When the king came down to Sumer the royal sojurn of Sar-kali-sarrē and the court of Akkad - Kraus, N. L. (2019)
At some point early on during his reign, Sar-kali-sarrē, made a journey to Sumer. The occasion was so momentous that an entire year was named in commemoration of the excursion. This paper investigates the evidence for that royal visitation, with special attention given to the administrative documents that record the king's sojourn at Girsu. The investigation also considers the rationale for the king's decision to make an expedition to Sumer and asserts that Sar-kali-sarrē may have undertaken the journey in order to begin his building works at the Ekur in Nippur. In addition, the paper identifies some of the highest officials of the Akkadian court who traveled with the king. These individuals are significant because they are usually conspicuous in administrative documents, and as such their presence can establish prosopographic synchronisms between Sargonic archives.
Keywords: Sar-kali-sarrē, Babylonien, König